The dynamics of child poverty in industrialised countries - Bradbury, Bruce; Jenkins, Stephen P.; Micklewright, John (Cambridge University Press, 2001)
A child poverty rate of ten percent could mean that every tenth child is always poor, or that all children are in poverty for one month in every ten. Knowing where reality lies between these extremes is vital to understanding the problem facing many countries of poverty among the young. This unique study goes beyond the standard analysis of child poverty based on poverty rates at one point in time and documents how much movement into and out of poverty by children there actually is, covering a range of industrialised countries - the USA, UK, Germany, Ireland, Spain, Hungary and Russia. Five main topics are addressed: conceptual and measurement issues associated with a dynamic view of child poverty; cross-national comparisons of child poverty rates and trends; cross-national comparisons of children's movements into and out of poverty; country-specific studies of child poverty dynamics; and the policy implications of taking a dynamic perspective